Fabrication of Lithium Substituted Copper Ferrite (Li-Cufe2o4) Thin Film as an Efficient Gas Sensor at Room Temperature - Casagrande-Denardin, J (Elsevier B.V., 2018)
A Li-CuFe2O4 thin film has a well-defined nanocrystalline structure with a crystallite size of ∼17 nm. The TEM and SEM images of the Li-CuFe2O4 thin film show a polyhedron shape of nanoparticles with uneven sizes, resulting in a significant change in its gas sensing characteristics such as sensitivity and sensor response. An optical analysis shows that the Li-CuFe2O4 thin film has a semiconducting nature, and the band gap of the thin film is determined to be 1.15 eV. The gas sensor analysis demonstrates repeatability of the sensing behavior of the Li-CuFe2O4 thin film and this ensures a reliable and efficient gas sensor at room temperature. © 2018 The Authors